2022
DOI: 10.1155/2022/3268386
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Prognosis and Immune Infiltration of Ovarian Cancer Based on Homeobox D Genes

Abstract: Background. Homeobox D (HOXD) genes were associated with cancer pathogenesis. However, the role of HOXD genes in ovarian cancer (OC) and the possible mechanisms involved are unclear. In this study, we analyzed the function and regulatory mechanisms and functions of HOXD genes in OC based on comprehensive bioinformatics analysis. Methods. Expression of HOXD1/3/4/8/9/10/11/12/13 mRNA was analyzed between OC tissue and normal tissue using ONCOMINE, GEO, and TCGA databases. The relationship between HOXD expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…R version 3.6.3 and ggplot2 version 3.3.3 (R Core Team, Vienna, Austria) were used for the statistical analysis and visualization [ 22 , 28 ]. The molecules were hsa-miR-335-5p [MIMAT0000765], and KCNQ1OT1 [ENSG00000269821].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…R version 3.6.3 and ggplot2 version 3.3.3 (R Core Team, Vienna, Austria) were used for the statistical analysis and visualization [ 22 , 28 ]. The molecules were hsa-miR-335-5p [MIMAT0000765], and KCNQ1OT1 [ENSG00000269821].…”
Section: Methodsmentioning
confidence: 99%
“…The molecules were hsa-miR-335-5p [MIMAT0000765], and KCNQ1OT1 [ENSG00000269821]. The data were miRNAseq data from the level 3 BCGSC miRNA Profiling in the TCGA LUAD project and the RNAseq data in the level 3 HTSeq-FPKM format from the TCGA LUAD project [ 9 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…RNAseq data were obtained from The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression Project (GTEx) by Toil process (14). Software was R (version 3.6.3) (statistical analysis and visualization) and R package was mainly ggplot2 [version 3.3.3] (for visualization) were used to analyze the differential expression of IRXs (15).…”
Section: Expression Of Irx Genes In Luadmentioning
confidence: 99%
“…The correlation between each two IRXs was assessed using the Pearson correlation coe cient (15,16). Statistical analysis and graphs were done with R software (version 3.6.…”
Section: Expression Of Irx Genes In Luadmentioning
confidence: 99%
“…Another study demonstrated that HOXD1 suppresses cell proliferation and cell‐cycle progress in kidney renal clear cell carcinoma (KIRC) based on in silico analysis and functional experiments (Cui et al, 2021a). In addition, HOXD1 was elevated in ovarian cancer tissues and correlated with tumor stage (Chen et al, 2022). Knockdown of HOXD1 could promote breast cancer metastasis (Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%